2019
DOI: 10.2214/ajr.18.20033
|View full text |Cite
|
Sign up to set email alerts
|

CT of Gastric Volvulus: Interobserver Reliability, Radiologists' Accuracy, and Imaging Findings

Abstract: OBJECTIVE. The objective of this study was to identify CT findings and determine interobserver reliability of surgically proven gastric volvulus. MATERIALS AND METHODS. This single-center retrospective study included 30 patients (21 women, nine men; mean age, 73 years old) with surgically proven gastric volvulus who underwent preoperative CT and 31 age- and sex-matched control subjects (21 women, nine men; mean age, 74 years old) with large hiatal hernias who were imaged for reasons other than abdominal pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…According to the literature, abdominal CT scan is currently the modality of choice for the diagnosis of gastric volvulus with high sensitivity and specificity, superior to the barium study, endoscopy, and the other modalities; there are 2 signs in abdominal CT scan of gastric volvulus used in its diagnosis: gastropyloric transition zone and abnormal location of the antrum. Other advantages of CT scan consist of the definition of the anatomical defect which allows surgery planning, assessment of gastric viability, and perforation which aids decision regarding the urgency of operative intervention and its 24 hours accessibility and rapidity [6] , [7] , [8] , [9] . Although CT scan was accessible in our center, we decided to make an emergent transfer of the patient to the operating room regarding his critical condition and considerable suspicion of gastric volvulus based on the presentation and X-rays findings.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, abdominal CT scan is currently the modality of choice for the diagnosis of gastric volvulus with high sensitivity and specificity, superior to the barium study, endoscopy, and the other modalities; there are 2 signs in abdominal CT scan of gastric volvulus used in its diagnosis: gastropyloric transition zone and abnormal location of the antrum. Other advantages of CT scan consist of the definition of the anatomical defect which allows surgery planning, assessment of gastric viability, and perforation which aids decision regarding the urgency of operative intervention and its 24 hours accessibility and rapidity [6] , [7] , [8] , [9] . Although CT scan was accessible in our center, we decided to make an emergent transfer of the patient to the operating room regarding his critical condition and considerable suspicion of gastric volvulus based on the presentation and X-rays findings.…”
Section: Discussionmentioning
confidence: 99%
“…8 En este caso, la presentación no fue la clásica, por lo cual no se logró un diagnóstico certero preoperatorio. Fue necesario realizar una tomografía axial computada (TAC), lo cual concuerda con el estudio de Mazaheri y colaboradores, donde se apoya su uso como el estudio de mayor sensibilidad y especificidad para el diagnóstico de VG, con una precisión de 90%, el hallazgo más importante es el punto de transición del pico pilórico, 14 confirma el diagnóstico con detalles anatómicos y posibles condiciones asociadas (hernias paraesofágicas, diafragmáticas, eventración diafragmática). En la etapa tardía del VG, el compromiso vascular puede resultar en hallazgos de isquemia gástrica, ulceración o fisuras de la mucosa gástrica.…”
Section: Discussionunclassified
“…Mientras que en fase aguda debe tratarse con intervención quirúrgica de emergencia, no hay pautas claras sobre el manejo del VG crónico. 11,14 El manejo inicial debe ser con descompresión con SNG, seguida de cirugía para comprobar la viabilidad gástrica, resecar si hay necrosis y realizar tratamiento quirúrgico definitivo: reducción de la rotación, gastrostomía, gastropexia y reparación de los defectos predisponentes. 17 En un estudio retrospectivo sobre pacientes con VG y manejo conservador a cinco años, se encontró que la recurrencia sintomática fue de 64%, pero ésta sólo es una opción para los pacientes con VG crónico, en especial los mayores de 60 años y con alto riesgo quirúrgico, 17 implica reducción o gastrostomía endoscópica percutánea más tratamiento procinético y antisecretor; sin embargo, existe un riesgo alto de perforación gástrica.…”
Section: Discussionunclassified
“…The choice of initial imaging study is significant when there is suspicion for GV, as diagnostic delay can lead to fatal complications. CT imaging is highly reliable and accurate, with two findings (a normal gastropyloric transition zone and the antrum in an abnormal location) with 100% sensitivity and specificity for the diagnosis of acute GV [ 18 , 19 ]. One retrospective study investigated radiologists’ accuracy of CT interpretation for GV, with reported 90% overall accuracy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging is highly reliable and accurate, with two findings (a normal gastropyloric transition zone and the antrum in an abnormal location) with 100% sensitivity and specificity for the diagnosis of acute GV [ 18 , 19 ]. One retrospective study investigated radiologists’ accuracy of CT interpretation for GV, with reported 90% overall accuracy [ 19 ]. Interestingly, radiologists were able to make the critical distinction between GV and large hiatal hernia, which are notoriously difficult entities to distinguish, and especially notable because most GV cases are associated with paraesophageal hernias.…”
Section: Discussionmentioning
confidence: 99%